Recent Progress of 2D Layered Materials in Water-in-Salt/Deep Eutectic Solvent-Based Liquid Electrolytes for Supercapacitors - Krishnakumar Melethil; Munusamy Sathish Kumar; Chun-Ming Wu; Hsin-Hui Shen; Balaraman Vedhanarayanan; Tsung-Wu Lin (Nanomaterials, 2023)
Supercapacitors are candidates with the greatest potential for use in sustainable energy resources. Extensive research is being carried out to improve the performances of state-of-art supercapacitors to meet our increased energy demands because of huge technological innovations in various fields. The development of high-performing materials for supercapacitor components such as electrodes, electrolytes, current collectors, and separators is inevitable. To boost research in materials design and production toward supercapacitors, the up-to-date collection of recent advancements is necessary for the benefit of active researchers. This review summarizes the most recent developments of water-in-salt (WIS) and deep eutectic solvents (DES), which are considered significant electrolyte systems to advance the energy density of supercapacitors, with a focus on two-dimensional layered nanomaterials. It provides a comprehensive survey of 2D materials (graphene, MXenes, and transition-metal oxides/dichalcogenides/sulfides) employed in supercapacitors using WIS/DES electrolytes. The synthesis and characterization of various 2D materials along with their electrochemical performances in WIS and DES electrolyte systems are described. In addition, the challenges and opportunities for the next-generation supercapacitor devices are summarily discussed.